Performance Evaluation of Integrated Deep Learning Web Platform for Dataset Training - Sukaridhoto, Sritrusta; Basuki, Dwi Kurnia; Yulianus, Heri; Budiarti, Rizqi Putri Nourma (Applied Technology and Computing Science Journal, 2020)
Along with the complexity of recent web site, many users cannot get the benefits. We developed Integrated Deep Learning Web Platform to help researcher to prepare dataset trainig for Tensorflow. However, the quality of a web site needs to be assessed. This paper proposes an implementation of WebQual 4.0 for evaluating Integrated Deep Learning Platform for Training Dataset (INDEF) quality. This method used the WebQual model that has some instruments. The instruments grouped the WebQual questions to be three main categories; usability, information and service interaction. From the research conducted can be evaluated that all respondents agreed Integrated Deep Learning Platform for Training Dataset web site met all the WebQual characteristics.